Effect of temperature on fatigue behaviour of self-compacting recycled aggregate concrete. (January 2022) - Sainz-Aja, Jose A.; Carrascal, Isidro A.; Polanco, Juan A.; Thomas, Carlos
Abstract: The most recommendable frequency range for concrete fatigue tests is between 1 and 15 Hz. It has been clearly established that performing the tests at low frequency (<1 Hz) reduces the fatigue limit because it increases test time and therefore, creep damage. On the other hand, there are not enough studies analysing tests above 15 Hz, which could greatly reduce test time. In this work, three recycled concretes were characterized, starting with the comparison between tests at moderate frequency (10 Hz) with tests at very high frequency (90 Hz). From these tests it was observed that, in all cases, the fatigue limit or fatigue life was notably lower in the case of performing the tests at high frequency. The test results show that, in the case of tests performed over the fatigue limit, the temperature of the specimens rises up to approximately 100 °C, while, in the case of tests performed with strength lower the fatigue limit, the temperature stabilises at around 65 °C. In order to analyse whether the temperature was the cause of the reduction in the fatigue limit, creep tests were carried out at 3 temperatures: 20, 65 and 100 °C, and it was possible to verify that creep damage became significantly greater as temperature was increased, and that this effect was emphasized in those cases where the concretes were made with recycled crushed concrete aggregates.